2016
DOI: 10.1684/epd.2016.0821
|View full text |Cite
|
Sign up to set email alerts
|

Duration of valproic acid monotherapy correlates with subclinical thyroid dysfunction in children with epilepsy

Abstract: Aim. To identify potential risk factors for the development of subclinical hypothyroidism following long‐term valproic acid monotherapy in children with epilepsy. Methods. Serum levels of thyroid‐stimulating hormone, free thyroxine, free triiodothyronine, thyreoglobulin antibodies, and thyroid peroxidase antibodies were determined in 41 patients and in 41 sex‐ and age‐matched healthy children. Results. Mean valproic acid treatment duration was 2.80±1.96 years. The valproic acid group had higher serum thyroid‐s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(92 reference statements)
2
4
0
Order By: Relevance
“…Vainionpaa et al demonstrated a reversal of raised TSH levels after discontinuation of the medication [ 14 ]. There was no association between serum valproate level and subclinical hypothyroidism, as in previous studies [ 6 , 15 ]. Though Kim et al demonstrated an association between valproate levels and subclinical hypothyroidism [ 13 ].…”
Section: Discussionsupporting
confidence: 75%
“…Vainionpaa et al demonstrated a reversal of raised TSH levels after discontinuation of the medication [ 14 ]. There was no association between serum valproate level and subclinical hypothyroidism, as in previous studies [ 6 , 15 ]. Though Kim et al demonstrated an association between valproate levels and subclinical hypothyroidism [ 13 ].…”
Section: Discussionsupporting
confidence: 75%
“…8,9,14,17 Yet other studies reported similar results to ours, showing an increase in TSH with normal fT4 levels. 18,19 In our study, we detected subclinical hypothyroidism in 16% of the children receiving VPA treatment, and none in the LEV group. Our results duplicate those previously reported in the literature which found a 12.5 to 28% frequency of subclinical hypothyroidism in children receiving VPA.…”
Section: Discussionsupporting
confidence: 49%
“…Our results duplicate those previously reported in the literature which found a 12.5 to 28% frequency of subclinical hypothyroidism in children receiving VPA. 9,14,18 AEDs might cause thyroid dysfunction via several mechanisms such as disturbing its biosynthesis, secretion, transport, metabolism, and excretion. 3,20 One of the most important mechanisms is the hepatic enzyme induction of the AEDs such as phenytoin and carbamazepine that increase the metabolism of thyroid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast with the observation by Yilmaz et al, we did not observe a decrease in frequency of subclinical hypothyroidism in patients receiving LEV. The duration of ASD therapy, age, daily dosage, and serum level of ASDs could be potential risk factors for thyroid dysfunction . Assessment of thyroid function in epileptic children would be helpful, because ASDs could influence thyroid dysfunction and development of subclinical hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%